Optimization of Legal Protection For Laku Pandai (Branchless Banking) As A Micro Business Empowerment Effort By OJK in The Central Region - S. Sulistyandari; Siti Muflichah; M Wiwik Yuni Hastuti (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2021)
The Laku PandaiProgram is a manifestation of OJK's commitment to support the Indonesian Government's programme of launching the National Strategy for Financial Inclusion, a part of which is branchless banking. Laku Pandai envisages provision of banking and / or other financial services not through an office network, but through cooperation with other parties and needs to be supported by the use of information technology facilities. Based on OJK data, the Laku Pandai programme has progressed; however, the Laku Pandai empowerment policy is still the focus of OJK in 2019-2020, because there are still several obstacles to its implementation. The Laku Pandai agent, as a micro business actor, needs empowerment. This study aims to examine legal protection, constraints, benefits and empowerment of the implementation of Laku Pandai. The research method used was normative and sociological juridical by the use of secondary and primary data, and data analysis using the normative qualitative method. The results of the study show that legal protection is not optimal, that there are several obstacles to the implementation of branchless banking from both agents and banks and that empowerment of micro branchless banking agents is very useful in achieving Government goals for the realization of inclusive finance in Indonesia.Keywords: Laku pandai, Legal Protection, Empowerment